Integration of FMEA method and overall equipment effectiveness to increase effectiveness of TS analyzer machine - Welly Atikno; Lien Herliani Kusumah (Jurnal Sistem dan Manajemen Industri, 2022)
Total Sulfur Analyzer (TS Analyzer) is one of the machines in the laboratory to test the total sulfur content contained in coal samples. Technically, specifications and use are regulated by international standards. In 2020, the downtime of these tools was very high, causing the productivity of surveyors to decrease. Low productivity will have an impact on the company's losses. The productivity of this equipment and machines is crucial to maintaining the company's success in its business processes. This study aims to measure the effectiveness of the operational performance of the TS Analyzer machine in the laboratory, analyze the causative factors and make improvements. This research uses the integration method of Failure Mode And Effect Analysis (FMEA) and Overall Equipment Effectiveness (OEE). Based on the analysis of the causes of the problem, the low OEE value is caused by the high breakdown loss. Based on the FMEA analysis, it was found that the operator was wrong in operating the machine with RPN 343, electrical instability with RPN 343, unstable temperature with RPN 343 and improper thermocouple installation. The results showed that the OEE value of the TS Analyzer machine has increased after the improvement.